Anti-allergic effects of two potential probiotic strains isolated from infant feces in China. (May 2022) - Liang, Huijing; Zhang, Yujie; Miao, Zhonghua; Cheng, Ruyue; Jiang, Fengling; Ze, Xiaolei; Shen, Xi; He, Fang
Graphical abstract: Highlights: Infant feces-derived bacterial strains acted on the host differentially. L. paracasei 207-27 showed stronger anti-allergic effects than LGG. L. paracasei 207-27 characteristically enriched Lactobacillaceae in allergic host. B. breve 207-1 showed potent immunomodulatory effects. Abstract: Abnormal cross-talk between the intestinal microbiota of host animals and their immunity is evidently associated with an increase in the prevalence of allergy, and some selected probiotics have been found to play a role in pertinent mechanisms. Herein we evaluated the anti-allergic effects and mechanisms of two newly identified strains isolated from infant feces, namely Bifidobacterium breve 207-1 (207-1) and Lacticaseibacillus paracasei 207-27 (207-27), in ovalbumin-sensitized mice. We found that 207-27 showed stronger anti-allergic effects than 207-1 and even Lacticaseibacillus rhamnosus GG, which could be attributed to enhanced systemic and intestinal mucosal immunity, restored intestinal microbiome, and enriched Lactobacillaceae.  In addition, 207-1 markedly enhanced splenic cytokine levels and partially restore microbial dysbiosis in allergic mice. To summarize, 207-27 and 207-1 could characteristically influence host immunity and intestinal microbiota in a strain-dependent manner. We believe that 207-27 is a promising probiotic strain considering its beneficial effects on the host.